ANALISA EFISIENSI PENGELOLAAN PARKIR DI KOTA AMBON - James Pelupessy (Jurnal Administrasi Terapan, 2023)
This research is intended to look at parking management without looking at its effectiveness which has been used so far but is measured at the level of efficiency. This measurement uses a management efficiency formula which uses a comparison of costs incurred with the actual receipt of parking fees. And 2021 is the lowest efficiency value, namely 7.42%, which can be used as a minimum benchmark in planning Keywords: Parking. Efficient